Compact wideband patch antenna and its MIMO configuration for 28 GHz applications - Hussain, Niamat; Awan, Wahaj Abbas; Ali, Wael; Naqvi, Syeda Iffat; Zaidi, Abir; Le, Tuan Tu (International journal of electronics and communications, 2021)
This article presents a printed antenna owing the advantages of compact size and simple geometrical configuration for fifth-generation (5G) 28 GHz communication systems. For better performance and miniaturization purposes, both the ground plane and the radiator of the patch antenna are defected with a rectangular slot. The antenna presents a wide operating bandwidth and high radiation efficiency while keeping reasonable gain. Furthermore, two elements Multiple-Input-Multiple-Output (MIMO) configuration of the proposed antenna was designed for MIMO applications. The MIMO antenna is also characterized by a good envelope correlation coefficient (ECC), low Channel Capacity Loss (CCL), and high diversity gain, which proves that the presented antenna can be seamlessly housed in miniaturized 5G smart devices. The proposed work is verified by experiments which are well-matched with predicted results. In comparison with other related works, the presented work is dominant in terms of wide operating bandwidth, high isolation, low ECC, and compact design.